Innovations in immunotherapy for autoimmune diseases: recent breakthroughs and future directions - Alsayb, May A. (Frontiers in Immunology, 2025)
Millions of people worldwide suffer from chronic and devastating autoimmune disorders, challenging contemporary medicine. These disorders develop when the immune system attacks its own tissues, causing inflammation and damage. Traditional treatments have focused on widespread immunosuppression, which can relieve symptoms but has serious adverse effects and does not address immunological dysregulation. This review discusses the current and future trends in immunotherapy for the management of autoimmune diseases, including advancements such as CAR T-cell therapy, bispecific antibodies, next-generation immune checkpoint modulators, targeted cytokine therapies, and microbiome-based interventions. The discussion is grounded in current scientific literature, focusing on mechanisms of action, recent breakthroughs, limitations, and potential future directions. Each of the related sections presents cutting-edge advancements, current challenges, and future opportunities for research and clinical translation.